Interventions performed by clinical pharmacist in the renal transplant ambulatory care - Diego Gnatta; Elizete Keitel; Isabela Heineck (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2019)
Introduction: The development of new immuno-suppressant agents and other supporting medications has increased the complexity of medical regimes. Therefore, potential drug interactions, adverse reactions and costs may jeopardize a successful outcome. Although pharmacists have been involved in the care of patients after transplants, only a few kidney transplant teams can count with dedicated pharmaceutical services. Objective: The goal of this study was to describe the pharmaceutical interventions performed to improve treatment outcomes of patients who underwent kidney transplantation. Methods: This study was a randomized clinical trial and was carried out in a specialized transplant hospital in southern Brazil. The clinical pharmacist followed up 64 patients during a period of 12 months and performed interventions when identifying a drug related problem. The pharmaceutical interventions were categorized as "significant", "very significant" or "extremely significant". Medication-related negative outcomes were classified in relation to their effectiveness, safety and necessity. Results: Two hundred and twenty-six (226) pharmaceutical interventions were performed, with a mean of 3.25 ± 2.37 per patient. Among them, 159 (70.4%) were patient-oriented, and 67 (29.6%) were health teamoriented. Thirty eight percent were classified as very significant. Frequent pharmaceutical interventions performed were to suggest the reduction of immuno-suppressant doses to the physicians, educate patients with post-transplant diabetes mellitus or in case of skipping doses. One hundred and fourteen (114) medication-related negative outcomes were identified, 43% related to effectiveness, 36% to safety and 21% to necessity. The number of acute rejection confirmed by biopsy was 33 (51.6%). The free survival of acute rejection was 59.4% in the first month, 53.1% in the third month and 48.3% in 12 months. Conclusions: The pharmacist has an important role in the ambulatory care of kidney transplant, identifying problems and acting as a major player towards the reduction of medication-related negative outcomes.